Post-Flood Challenges to Polio Eradication in Pakistan - Ahmed, Riaz; Nasir, Abdul Majid; Ayyoub, Muhammad; Ahmed, Adeel (Pakistan Journal of Humanities and Social Sciences, 2024)
This study aims to investigate the effect of flood on polio vaccination coverage among children aged 0-2 years in Pakistan, with a particular emphasis on the impact of floods on vaccination rates in both urban and rural areas, male and female, families of varying sizes, families with educated and uneducated heads, and the socio-economic status of households. The study utilized household-level data from the Pakistan Social and Living Standards Measurement surveys conducted between 2004-05 and 2014-15. Difference-in-Differences (DID) analysis and inverse probability of treatment weighting (IPTW) were employed, treating the flood as a quasi-natural experiment. The flood in 2010 in Pakistan disrupted polio vaccination coverage significantly; particularly in rural areas and among households led by uneducated parents. During the flood, 135 out of 1000 children aged 0-2 years were not fully vaccinated against poliovirus, and this number varied across different regions and family sizes with 171 fewer children per 1000 fully vaccinated during the flood in rural flooded areas. The adverse effects persisted for several years, with disparities observed based on parental education, gender, and household assets. Despite some recovery, the decline in polio immunization coverage remained significant in the years following the flood, especially in large families and impoverished households. Disparities based on gender, socioeconomic status, parental education, and family size were evident. Regardless of global efforts to combat polio, natural disasters like floods pose significant challenges to immunization programs, emphasizing the need for targeted interventions and improved disaster preparedness in vulnerable regions.